ASUHAN KEPERAWATAN PADA NY.W (G3P2A0) DENGAN ANEMIA TRIMESTER III KEHAMILAN DI WILAYAH PONDOK PETIR KOTA DEPOK - Annisa Nur Kasanah, (2023)
Background: Anemia is a condition where the number of red blood cells is reduced due to blood loss that is too fast or can also be caused by the production of red blood cells which is too slow or too small. Most of the problems of pregnant women are caused by iron deficiency due to a lack of input of iron elements in food. Knowing the causal factors and how to handle anemia in pregnant women with orphanages in order to reduce the incidence and risk due to anemia in pregnant women. One of the factors in the maternal mortality rate (MMR) is the occurrence of bleeding during childbirth which is characterized by anemia during pregnancy. The purpose of this study was to provide care services for pregnant woman Mrs.W (G3P2A0) with anemia in the Pondok Lightning area, Depok City. This research design uses qualitative methods in implementing your care for Mrs. W (G3P2A0) third trimester of pregnancy in the Pondok Petir area, Depok City February 23, 2023- February 28, 2023. Data collection was carried out by interviews, observation, and physical examination, as well as documentation of clients directly with a sample of 1 respondent. The results of the study found that most pregnant women with anemia had signs and symptoms, one of which was fatigue when doing physical activity, and unhealthy sleep patterns. Therefore, it can be said that the relationship between anemia in pregnant women and patterns of physical activity, and sleep patterns are interrelated. Conclusion: Anemia in pregnancy can be reduced by reducing client complaints of signs and symptoms after nursing care is carried out and evaluation is carried out with SOAP documentation. Keywords: Pregnancy, Anemia, Nursing Care